Pelayanan Antenatal Care Terpadu bagi Ibu Hamil di IIKNU Tuban sebagai Upaya Peningkatan Kesehatan Ibu dan Janin - Qoyimah, Ilmiatus; safa'ah, nurus (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Maternal health is a critical indicator of healthcare quality in a region. In Tuban Regency, Indonesia, integrated antenatal care (ANC) services remain underutilized due to limited access and insufficient awareness among pregnant women. This community engagement initiative aimed to address these gaps by implementing a comprehensive ANC program at the IIKNU Tuban campus. The program involved 30 pregnant women who participated in health check-ups, nutritional counseling, and early detection of complications such as pre-eclampsia and anemia. Educational sessions and personalized consultations emphasized the importance of routine ANC visits and healthy pregnancy practices. The results indicated significant improvements: 85% of participants reported increased awareness about ANC, 10% benefited from early detection of complications, and 90% appreciated the ease of access provided by the campus-based location. These outcomes highlight the effectiveness of integrating healthcare services within educational institutions to enhance maternal and fetal health, particularly in undeserved areas. This initiative offers a callable model for addressing maternal health challenges and underscores the value of localized health interventions.